Enhanced photodynamic therapy of TiO2/N-succinyl-chitosan composite for killing cancer cells - Ma, Min (2022)
The aim of this study was to investigate the effect of TiO2/N-succinyl-chitosan composite (TiO2/ NSCS) photodynamic therapy (PDT), while considering the effects of various light sources on the activation of photosensitizer. The methyl thiazolyl tetrazolium assay was used to examine the cell survival rate of the cells. The results showed that glioma cell strain (U251) was the most sensitive cancer cell strain to TiO2/NSCS. When the concentration of TiO2/NSCS was between 0 and 800 μg·mL-1, there was no obvious cytotoxicity to normal liver cells (HL-7702) and U251 cells. During the PDT process, the photokilling effect of TiO2/NSCS on U251 cells under ultraviolet-A (UVA) light irradiation was stronger than that of pure TiO2, and its killing effects were positively correlated with concentration and irradiation time. In addition, both UVA and visible light could excite TiO2/ NSCS, which had significant killing effect on U251 cells. The results of acridine orange/ethidium bromide fluorescent double staining and Annexin V/propidium iodide double staining indicated that TiO2/NSCS under UVA and visible light irradiation could kill U251 cells by inducing apoptosis, and the apoptosis rate of TiO2/NSCS treatment groups was higher than that of TiO2 treatment groups. Therefore, TiO2/NSCS might be used as a potential photosensitizer in PDT.